(3GdeTcGI GdZQhjI aj TQM GddeYI GdOeTbjIs - (3edG cJGH, eMeO LhGO Hf eMeO Jbj Hf eMeO GdCMeOj, cGf MjG (B1267(3g` (B1851(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3jLH (B... (3bOeg Ydi GdfjI hGdJcHjQ dhLhHg bHdgeG HGdJHY hdchfg TQWG ajgeG hGdTQW ebOe Ydi GdeTQhW hBNQg aj GdPcQis
(3BNQgG (B:s
(3BNQgG(B: (3heG cGf efgG ef ZjQ PhGJ GdCSHGH cSdhI GdfHj hYdj haGWeI Ydjge GdSdGe hLYaQ hZjQ Pdc eG PcQg GdUMGH aj cJHge GdeWhdI hcJH GdCYeGd hdG MUQ dfbd GdSdhI aEfgG bQHGf cd fbj hNjQ ehVhY aef TGA GSJbd hef TGA GSJcKQ ceG Sda HjGfg aj Chd GdcJGHs
(3JHUQI GdYfhGf (B:s
(3hjSei CjkVG(B: (3GdCfhGQ GdZQhjI, hjSei CjkVG(B: (3GdQTjYI GdfHhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 201s
(3GdPQjYI, L (B21: 41s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis